Penyelesaian Wanprestasi Dalam Perjanjian Kredit Dengan Jaminan Hak Tanggungan - Thomas Adrian Doing; Celina Tri Siwi K; Hermanto Silalahi (Comprehensive Law Journal, 2023)
The purpose of this research is to find out the legal settlement of the default in the credit agreement at Obor Mas Maumere Credit Cooperative and to know the inhibiting factors for the settlement of defaults in the loan agreement with guaranteed Mortgage Rights.The research method used is an empirical juridical research,with a sosiological juridical approach method,.According to the results of the research obtained,the settlement of defaults in the loan agreement with guaranteed Mortgage at Obor Mas Maumere Credit Cooperative is carried out through two ways of settlement, namely through non-litigation and litigation channels.calling of the debtor and through credit coaching by investigating the causes of late payment. If the effort to save credit by rescheduling is not successful,the solution taken by the Obor Mas Credit Cooperative is through legal channels (litigation).With the procedure,give a warning letter first ( SP1,2,3),if there is no settlement from the borrower,the next step is the execution of collateral. The execution process can be through Execution by selling under the hand directly,Execution through the State Wealth and Auction Service Office (KPKNL) and Execution through the District Court.The inhibiting factors that arise in the settlement process come from the debtor himself,the non-cooperative debtor hides / loses intentions by the debtor to delay the mediation with the Credit Cooperative and ignores the warning letter given by the Credit Cooperative,lack of understanding by the debtor regarding settlement steps default in the credit agreement offered by the Credit Cooperative so that it is difficult to obtain an agreement.The issuer usually makes if difficult to hand over the collateral, does not even vacate the collateral object that will be auctioned.from collateral takes a long time.